Towards Understanding Economic Growth in Indonesia: Reinterpretation Of Lewis Model In Improving Lingving Standars of Agricultural Sector Workforce Evidence From Indonesia - Reni Furwanti; Hardiyono Hardiyono; Dini Maulana Lestari (Hasanuddin University, 2021)
Agricultural has a prominent role in maintaining the equilibrium of economic condition. Nevertheless, most people have a tendency that this agricultural sector is not prospective enough in improving their living standard, then they decide to be an employee which is already crowded. Thus, this study will discuss and learn about Lewis's model of two-sector economics regarding to reinterpretation of this condition. The purpose of this research is to formulate the right model in improving the standard of living of agricultural sector workers. In this study will use quantitative methods with descriptive analysis to develop the models offered by Lewis. The results obtained by minimizing the massive transformation of agricultural sector workers to industrial sector workers can reduce the inequality in terms of employment. Where agricultural sector workers can upgrade their skills with the help of government social programs, namely labor-intensive programs so that farmers can prosper without leaving their main professions to become farmers, so that the employment sector industry does not expand (especially in urban industries).